Implementasi Metode Iqra’ dalam Pengajaran Al-Qur’an di Madrasah Diniyah Awaliyyah Al-Ikhlas Bendosukun Desa Slaharwotan Lamongan - Ani Masrikah; Fendi Krisna Rusdiana (Jumat Ekonomi: Jurnal Pengabdian Masyarakat, 2021)
Madrasah Diniyah Awwaliyah "Al-Ikhlas" Hamlet Bendosukun Slaharwotan Village is an educational institution for teaching the Qur'an which is located in the hamlet of Bendosukun, Slaharwotan Village, Ngimbang District, Lamongan Regency, East Java. The purpose of the establishment of this Madrasah is to make early childhood to teenagers become intelligent generations and know and be able to read the Qur'an. The service carried out at the Madrasah Diniyah "Al-Ikhlas" Bendosukun Hamlet was motivated by the ability of students to read the Qur'an which was still deemed inappropriate. So in this case the researcher wants to apply the learning of the Qur'an with the Iqro method which is expected to be able to make students more precise and appropriate in reading the Qur'an. Al-Qur'an learning using the iqro' method at Madrsah Diniyah Awaliyyah "Al-Ikhlas" Bendosukun Hamlet uses a private method, namely Santri reads the subject matter in front of the ustad/ah then listens to the ustad/ah and takes turns. From the results of the dedication that has been carried out, it is found that the application of the iqro' method at the Awaliyyah Madrasah "Al-Ikhlas" Bendosukun hamlet is quite good, this is indicated by the enthusiasm and enthusiasm of the students in learning the Qur'an using the iqro' method. In addition, many students at Madrasah Diniyah "Awaliyyah" have completed learning the Qur'an with the Iqro method so that they are able to read the Qur'an properly and correctly. Because the application of this method has been done since time immemorial. Factors supporting the application of the iqro' method at Madrasah Diniyah Awaliyyah "Al-Ikhlas" Bendosukun: 1) The iqro' method has been applied since time immemorial. 2) The iqro' method is easier to practice than other methods. 3) Ustad/ah who teach the iqro' method does not require special training or skills. 4) The community is very accepting and supports the application of the Iqro 'method.